2022
DOI: 10.1037/ccp0000699
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioral stress management effects on prenatal anxiety among low-income women.

Abstract: Objective: Few studies have tested cognitive behavioral therapy to reduce prenatal anxiety despite substantial empirical support among individuals seeking treatment for anxiety symptoms. We examined whether a brief cognitive behavioral intervention delivered to low-income pregnant women would be efficacious for reducing prenatal anxiety. Method: A sample of 100 primarily ethnic and racial minority pregnant women with subclinical anxiety (74% Latina, 18% Black; M age = 26.5) were randomized to an 8-week cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 88 publications
(115 reference statements)
0
5
0
Order By: Relevance
“…To investigate the potential impact of outliers, an influence analysis was also conducted. This identified four potential influential outliers (Bayat et al, 2021; Ponting et al, 2022; Shahsavan et al, 2021; Zemestani & Fazeli Nikoo, 2019). When these studies were omitted, the overall effect size was reduced ( d = −0.60) as were the confidence intervals (−0.91 to −0.29), albeit still significant, as well as reduced heterogeneity (87.4%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To investigate the potential impact of outliers, an influence analysis was also conducted. This identified four potential influential outliers (Bayat et al, 2021; Ponting et al, 2022; Shahsavan et al, 2021; Zemestani & Fazeli Nikoo, 2019). When these studies were omitted, the overall effect size was reduced ( d = −0.60) as were the confidence intervals (−0.91 to −0.29), albeit still significant, as well as reduced heterogeneity (87.4%).…”
Section: Resultsmentioning
confidence: 99%
“…To account for outliers, the above analysis was re‐run with the omission of the Zemestani and Fazeli Nikoo (2019), Shahsavan et al (2021), Bayat et al (2021) and Ponting et al (2022)studies. For group interventions, the overall effect size for the effect of intervention versus control reduced to d = −0.82 (95% CI = −1.33 to −0.23), indicating a medium effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-pharmacological and pharmacological interventions are available for this purpose. In a study by Ponting et al it was reported that the level of state anxiety was lower in women who were trained for stress management compared to those who did not complete the intervention 18 . Shen et al reported that the anxiety level of the pregnant women who were given five needs-based education programs by trained researchers was significantly lower than that of the control group 19 .…”
Section: Discussionmentioning
confidence: 98%